A nanofiltration membrane based on a porous reactive intermediate layer and its preparation method and application
By using two-dimensional nanosheets with rich porosity M-TCPP as the intermediate layer material in the nanofiltration membrane, the problem of permeation of aqueous phase monomers during interfacial polymerization is solved, and the permeability and ion selectivity of the membrane are improved, achieving more efficient separation performance.
Patent Information
- Application Number
- CN202311604790.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-28
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2043-11-28
AI Technical Summary
During the interfacial polymerization process of existing nanofiltration membranes, aqueous monomers permeate into the pores of the support layer, resulting in a thicker polyamide layer, hindering the transportation of water, and having a lower selectivity for ions of different valence states.
Two-dimensional nanosheet M-TCPP with rich porosity and carboxyl groups on the edge of the sheet are used as the intermediate layer material, and is deposited on the ultrafiltration base membrane through pressure-assisted filtration. The physical and chemical properties of the membrane surface are controlled by controlling the deposition amount of M-TCPP, and participate in the interface polymerization reaction, and change the pore size distribution and negative electrical properties of the membrane surface to improve separation ability.
The permeability of the nanofiltration membrane and the selectivity for single/dual ions are improved, the "funnel" effect and interface transmission resistance are solved, and the stability and separation performance of the membrane are enhanced.
Smart Images

Figure CN117504615B_ABST
Abstract
Description
Technical Field
[0001] This invention discloses a nanofiltration membrane based on a porous reactive intermediate layer, belonging to the field of separation membrane preparation and application technology. Background Technology
[0002] The ultrathin polyamide selective layer formed on the ultrafiltration support layer is the core of the separation between the composite nanofiltration membrane and the reverse osmosis membrane. Among them, nanofiltration membranes, due to their specific pore size distribution and surface charge characteristics, can separate monovalent / multivalent ions and chemical substances of different molecular weights, and have been widely used in wastewater treatment, drinking water purification, heavy metal ion removal, and seawater desalination pretreatment.
[0003] Nanofiltration membranes primarily consist of a polyamide separation layer prepared at the water-oil interface through interfacial polymerization of aqueous and oil-phase monomers. This layer possesses certain permeability and separation properties. Adjusting the interfacial polymerization conditions can improve the separation efficiency or enhance the permeability of the nanofiltration membrane. However, during interfacial polymerization, aqueous monomers can permeate into the pores of the support layer, forming polyamide within it. This results in a relatively thick polyamide layer, prolonging the water transport path and hindering water transport, thus becoming an obstacle to the preparation of highly permeable nanofiltration membranes.
[0004] Constructing an intermediate layer on the support layer can reduce the infiltration of aqueous monomers into the pores, solving the "funnel" effect. It can also reduce the interfacial resistance between the polyamide layer and the support layer, improving membrane permeability and balancing the inherent "trade-off" effect. Patent CN 111992039 A prepares a ZIF-8 intermediate layer on a porous substrate using a water / oil interface synthesis method and then prepares a polyamide separation layer on the ZIF-8 layer using interfacial polymerization. This increases water flux but results in low selectivity for monovalent / divalent ions. Patent CN 110801736 A prepares an HKUST-1 intermediate layer on the surface of a polyimide porous base membrane containing a large amount of amino groups using an in-situ growth method and then prepares a separation layer on the intermediate layer using interfacial polymerization, thus obtaining a nanofiltration membrane with excellent permeability, but its ion selectivity remains low. Both of these technical solutions prepare the intermediate layer through in-situ reaction. Since the membrane preparation process cannot be pressurized and cannot withstand prolonged high temperatures, the nanomaterials that require heating to form are difficult to grow directly in-situ on the base membrane. Summary of the Invention
[0005] To improve the permeability of nanofiltration membranes and enhance their selectivity for ions of different valence states, this invention employs two-dimensional nanosheets (M-TCPP) with abundant porosity and carboxyl-rich edges as the interlayer material. These nanosheets are deposited on an ultrafiltration membrane via pressure-assisted filtration. By controlling the deposition amount of the two-dimensional nanosheets—that is, the amount participating in the interfacial polymerization reaction—the physicochemical properties of the membrane surface are regulated. This alters the conditions of the interfacial polymerization reaction platform, such as the pore size, hydrophilicity, and reactivity of the support layer surface, thereby changing the pore size distribution on the membrane surface. This enhances the negative charge on the membrane surface, improving its ability to separate monovalent and divalent ions. Simultaneously, it addresses the "funnel" effect, reduces interfacial transport resistance, and improves membrane permeability.
[0006] To achieve the above objectives, the present invention adopts the following technical solution:
[0007] A nanofiltration membrane based on a porous reactive intermediate layer comprises, from bottom to top, a base membrane, a porous two-dimensional nanomaterial layer with active reactive sites, and a polyamide separation layer. The porous two-dimensional nanomaterial with active reactive sites is M-TCPP, where M is a metal. The polyamide separation layer is formed by the reaction of polyamines and polyacrylamide chlorides, as well as the reaction of the polyamines and carboxyl groups in M-TCPP.
[0008] A method for preparing a nanofiltration membrane based on a porous reactive intermediate layer specifically includes the following steps:
[0009] (1) Preparation of porous reactive intermediate layer: The porous two-dimensional nanomaterial with active reactive sites is uniformly deposited on the surface of the base film by pressure-assisted filtration and then naturally dried until there are no liquid droplets on the surface for later use.
[0010] (2) Preparation of nanofiltration membrane based on intermediate layer: a polyamide separation layer is generated on an intermediate layer with porous reactivity through interfacial polymerization reaction.
[0011] Specifically, the process involves sequentially impregnating an aqueous solution containing polyamines and an organic solution containing polyacrylamide chlorides onto a porous, reactive intermediate layer, resulting in interfacial polymerization. After post-treatment, a composite nanofiltration membrane is obtained. During the interfacial polymerization process, in addition to the reaction between the amine groups of the aqueous monomers and the acrylamide chlorides of the oil monomers, the carboxyl groups in the two-dimensional nanomaterial M-TCPP also react with the amine groups.
[0012] M includes, but is not limited to, Zn, Cd, Co, Fe, Al, Cu, etc., such as any one of Zn-TCPP, Cd-TCPP, Co-TCPP, Fe-TCPP, Al-TCPP, and Cu-TCPP, whose plates carry carboxyl groups. The M-TCPP is prepared by a hydrothermal reaction using metal M salts, meso-tetra(4-carboxyphenyl)porphyrin, pyrazine, and polyvinylpyrrolidone as raw materials.
[0013] In step (1), the loading of porous two-dimensional nanomaterials with active reaction sites is 10–150 mg·m³. -2 20–120 mg·m -2 45–113 mg·m -2 63~113mg·m -2 23~113mg·m -2 The pore size is 1–5 nm.
[0014] The pressure applied during the pressure-assisted filtration process is 0.1–0.3 MPa, and the deposition time is 10–30 min.
[0015] The base membrane is an existing porous support membrane, such as an ultrafiltration membrane made of polysulfone, polyethersulfone, polyvinylidene fluoride, etc.
[0016] In step (2), the polyamine and polyacrylamide chloride are substances known to those skilled in the art capable of interfacial polymerization. The polyamine includes, but is not limited to, any one of ethylenediamine, hexamethylenediamine, piperazine, m-phenylenediamine, p-phenylenediamine, polyethyleneimine, and diethyltriamine; the polyacrylamide chloride includes, but is not limited to, any one of trimesoyl chloride, 3,4′,5-biphenyltriacryl chloride, 3,3′,5,5′-biphenyltetramethyl chloride, isophthaloyl chloride, 5-isocyanate isophthaloyl chloride, and 5-oxoformyl chloride isophthaloyl chloride. The concentration of the polyamine in the aqueous solution is 0.5–2%, and the concentration of the polyacrylamide chloride in the organic solution is 0.05–0.2%.
[0017] Furthermore, in step (2), the aqueous phase immersion time is 1-5 min, the organic phase immersion time is 0.5-3 min, the post-treatment temperature is 60-90℃, and the time is 2-5 min.
[0018] Furthermore, the application of the nanofiltration membrane based on the porous reactive intermediate layer in the selective separation of mono / divalent anions is demonstrated by its application in Cl... - / SO 2 4 - Separation field, Cl - / SO 2 4 - The separation factor is 40–80, and the water flux is 5–8 L·m. -2 ·h -1 ·bar -1 .
[0019] Compared with the prior art, the present invention has the following beneficial effects: (1) Compared with the preparation of mixed matrix membrane by incorporating nanomaterials into the aqueous phase, forming an intermediate layer by pressure-assisted method can reduce the loss of nanomaterials, and solve the problem of defects in the polyamide layer caused by the aggregation of nanomaterials. It also solves the problem that the nanomaterials in the polyamide layer are easily damaged when the nanofiltration membrane is acid-alkali cleaned. More importantly, the intermediate layer formed between the polyamide layer and the base membrane solves the "funnel" effect; (2) Compared with non-porous materials such as graphene and graphene oxide, the inherent pores of porous nanosheets can provide additional water transport channels, improve the permeability of the membrane, and have good organic compatibility, without causing membrane defects; (3) Constructing a porous intermediate layer can prevent aqueous monomers from penetrating into the pores of the ultrafiltration membrane, prevent the formation of polyamide in the pores, reduce the water transport resistance, and further improve the permeability; (4) By constructing a reactive intermediate layer, the carboxyl groups on the periphery of the intermediate layer participate in the interfacial polymerization reaction, so that a Turing structure is formed on the membrane surface, the hydrophilicity of the membrane surface is improved, the pore size distribution is widened, the electronegativity is enhanced, etc., which improves the resistance to Cl. - / SO 2 4 - (5) Compared with the existing ZIF-8 material, M-TCPP participates in interfacial polymerization and has good interlayer bonding force, which makes the nanofiltration membrane have good stability and at the same time changes the hydrophilicity of the membrane material. Attached Figure Description
[0020] Figure 1 This is a SEM image of the membrane surface in Comparative Example 1.
[0021] Figure 2 This is a SEM image of the membrane surface in Example 4. Detailed Implementation
[0022] The technical solution of the present invention will be further described below with reference to the accompanying drawings and embodiments. Obviously, the described embodiments are only some, not all, of the embodiments of the present invention.
[0023] Comparative Example 1:
[0024] A method for preparing a nanofiltration membrane, specifically comprising:
[0025] A 1.0 wt% piperazine aqueous solution was uniformly poured onto the surface of the polysulfone membrane. After standing for 1 min, the solution was poured off and allowed to air dry. Then, a 0.2 wt% trimesoyl chloride organic solution was poured onto the membrane surface. After reacting for 1 min, the organic phase was poured off and the membrane was heat-treated in an 80℃ oven for 3 min. The membrane was then immersed in deionized water for 12 h for testing and characterization. The performance of the prepared polyamide nanofiltration membrane was evaluated. At room temperature and 0.5 MPa, the nanofiltration membrane achieved a salt rejection rate of 98.21% for 2000 ppm sodium sulfate and a water flux of 16.31 L·m⁻¹.-2 ·h -1 The Cl in a mixed solution of 1000 ppm sodium sulfate and 1000 ppm sodium chloride - / SO 2 4 - The separation factor was 39.62.
[0026] Example 1:
[0027] A method for preparing a nanofiltration membrane based on a porous reactive intermediate layer, specifically comprising:
[0028] 45 mg Zn(NO3)2·6H2O, 8 mg pyrazine, and 100 mg polyvinylpyrrolidone were dissolved in a mixed solution of 15 mL ethanol and 45 mL N,N-dimethylformamide. Separately, 20 mg TCPP was dissolved in a mixed solution of 5 mL ethanol and 15 mL N,N-dimethylformamide. Each solution was sonicated for 10 min. The TCPP organic ligand solution was then added dropwise to the Zn(NO3)2·6H2O solution, and sonicated for another 10 min. After thorough mixing, the mixture was placed in an 80 °C oven for 18 h. After the reaction, the supernatant was removed by centrifugation. The sample was washed three times with ethanol and then dried in a 60 °C oven for 12 h to obtain Zn-TCPP with pore sizes concentrated between 2.8 nm and 4.6 nm.
[0029] Zn-TCPP, a porous two-dimensional nanomaterial with carboxyl-active reactive sites, was selected as the intermediate layer material. Zn-TCPP nanosheets were deposited onto the polysulfone membrane surface using pressure-assisted filtration, with a deposition amount of 22.63 mg·m³. -2 The auxiliary pressure is 0.1 MPa, and the pressurization time is 20 min.
[0030] Experimental tests show that the pore size of the polysulfone membrane surface is concentrated at around 16 nm, while the pore size of Zn-TCPP is mainly concentrated at 2.8 nm and 4.6 nm. Pressure filtration alters the pore size of the membrane surface. Furthermore, because Zn-TCPP carries carboxyl groups, which are hydrophilic, negatively charged, and participate in interfacial polymerization reactions, it changes the conditions of the interfacial polymerization reaction platform, such as the pore size, hydrophilicity, and reactivity of the support layer surface.
[0031] After air-drying until no droplets remain on the surface, a 1.0 wt% piperazine aqueous solution was uniformly poured onto the surface of the Zn-TCPP interlayer. After standing for 1 minute, the aqueous solution was poured off, and the membrane was air-dried again. Then, a 0.2 wt% trimesoyl chloride organic solution was poured onto the membrane surface. After reacting for 1 minute, the organic phase was poured off, and the membrane was heat-treated in an 80℃ oven for 3 minutes. After heat treatment, the membrane was immersed in deionized water for 12 hours for testing and characterization. The performance of the prepared Zn-TCPP interlayer nanofiltration composite membrane was evaluated. At room temperature and 0.5 MPa, the nanofiltration membrane achieved a salt rejection rate of 98.25% for 2000 ppm sodium sulfate and a water flux of 26.20 L·m⁻¹. -2 ·h -1 The Cl in a mixed solution of 1000 ppm sodium sulfate and 1000 ppm sodium chloride - / SO 2 4 - The separation factor is 45.29.
[0032] Examples 2-5
[0033] Examples 2-5 are identical to Example 1 except for the number of deposited Zn-TCPP nanosheets. The different deposition amounts and performance results are shown in Table 1.
[0034] Example 6
[0035] Example 6 is the same as Example 1 except that the two-dimensional nanomaterial Cu-TCPP is used as the intermediate layer material.
[0036] Table 1 shows the Zn-TCPP loading, membrane water flux, sodium sulfate rejection ratio, and Cl... - / SO 2 4 - A table showing the data correspondence between separation factors. From the table, it can be seen that with the increase of the number of Zn-TCPP nanosheets, water flux, salt rejection rate, and Cl... - / SO 2 4 - The separation factor showed an increasing trend, but in Example 5, the water flux, salt rejection rate, and Cl... - / SO 2 4 - The separation factor was slightly lower than that in Example 4, indicating that an appropriate deposition amount can achieve optimal membrane performance.
[0037] Figure 1 The results show that the surface morphology of the polyamide film in Comparative Example 1 is a micro-nodular structure with uniform nodule size and even distribution.
[0038] Figure 2 The surface morphology of the Zn-TCPP intermediate nanofiltration membrane exhibits a Turing structure, along with large nodules.
[0039] Table 1
[0040]
Claims
1. A method for preparing a nanofiltration membrane based on a porous reactive intermediate layer, characterized in that: The following steps are involved: (1) Preparation of a porous reactive intermediate layer: A porous two-dimensional nanomaterial having active reactive sites is uniformly deposited on the surface of a polysulfone membrane by pressure-assisted filtration, and the membrane is naturally dried until there are no droplets on the surface for later use. The porous two-dimensional nanomaterial having active reactive sites is Zn-TCPP. The preparation method of Zn-TCPP is as follows: using metal Zn salt, meso-tetra(4-carboxyphenyl)porphine, pyrazine and polyvinylpyrrolidone as raw materials, performing a hydrothermal reaction, and centrifuging to obtain a precipitate, namely Zn-TCPP. The loading amount of Zn-TCPP on the base membrane is 45.26-113.15 mg·m -2 ; (2) Preparation of nanofiltration membrane based on intermediate layer: An aqueous solution containing polyamine and an organic solution containing polyacyl chloride are sequentially impregnated on the intermediate layer with porous reaction activity to cause interfacial polymerization reaction. After post-treatment, a composite nanofiltration membrane is obtained. The concentration of polyamine in the aqueous solution is 0.5-2%, and the concentration of polyacyl chloride in the organic solution is 0.05-0.2%; In the step (2), the immersion time of the aqueous solution is 1 to 5 min, the immersion time of the organic solution is 0.5 to 3 min, and the post-treatment temperature is 60 to 90° C. and the time is 2 to 5 min.
2. The method for preparing a nanofiltration membrane based on a porous reactive intermediate layer according to claim 1, characterized in that: The polyamine includes any one of ethylenediamine, hexamethylenediamine, piperazine, m-phenylenediamine, p-phenylenediamine, polyethyleneimine, and diethylenetriamine; the polyacyl chloride includes any one of trimesoyl chloride, 3,4′,5-biphenyltrichloride, 3,3′,5,5′-biphenyltetrachloride, isophthaloyl chloride, 5-isocyanate isophthaloyl chloride, and 5-oxycarbonyl chloride isophthaloyl chloride.
3. The method for preparing a nanofiltration membrane based on a porous reactive intermediate layer according to claim 1, characterized in that: The pressure applied during pressure-assisted filtration was 0.1~0.3 MPa, and the sedimentation time was 10~30 min.
4. A method for preparing a nanofiltration membrane based on a porous reactive intermediate layer, characterized in that: (1) 45 mg Zn(NO3)2·6H2O, 8 mg pyrazine, and 100 mg polyvinylpyrrolidone were dissolved in a mixed solution of 15 mL ethanol and 45 mL N,N-dimethylformamide. 20 mg TCPP was dissolved in a mixed solution of 5 mL ethanol and 15 mL N,N-dimethylformamide. Each solution was ultrasonicated for 10 min. The TCPP organic ligand solution was added dropwise into the Zn(NO3)2·6H2O solution and ultrasonicated for 10 min. After mixing evenly, the mixture was placed in an oven at 80°C for 18 h. After the reaction, the upper layer of the solution was removed by centrifugation. The sample was washed with ethanol three times and dried in an oven at 60°C for 12 h to obtain Zn-TCPP. Zn-TCPP nanosheets were deposited on the surface of the polysulfone membrane by pressure-assisted filtration. The deposition amount was 45.26-113.15 mg·m -2 , the auxiliary pressure is 0.1MPa, and the pressurization time is 20 min; (2) After naturally drying until there are no droplets on the surface, pour 1.0 wt% piperazine aqueous solution evenly on the surface of the Zn-TCPP intermediate layer. After standing for 1 min, pour out the aqueous solution. After naturally drying, pour 0.2 wt% trimesoyl chloride organic solution on the membrane surface. After reacting for 1 min, pour out the organic phase and place it in an oven at 80 ° C for heat treatment for 3 min. After heat treatment, soak the membrane in deionized water for 12 h.
5. A nanofiltration membrane based on a porous reactive intermediate layer prepared by the method according to any one of claims 1 to 4.
6. Use of the nanofiltration membrane based on the porous reactive intermediate layer as claimed in claim 5 in the selective separation of monovalent and divalent anions.
Citation Information
Patent Citations
Preparation method of organic solvent resistant nanofiltration membrane not prone to being stripped
CN110801736A
Method for preparing high-performance nanofiltration membrane by constructing ZIF-8 intermediate layer
CN111992039A